Penerapan Biopori pada Halaman Rumah Warga RT.01 RW.04 Desa Kuwaron Kecamatan Gubug Kabupaten Grobogan Jawa Tengah - Talitha Zhafira; Ahmad Hakim Bintang Kuncoro; Bambang Purnijanto; Retno Dewi Pramodia Ahsani (Jurnal Pengabdian KOLABORATIF, 2023)
The people of Kuwaron Village, especially residents of RT.01 RW.04, have recently had problems of environmental damage, namely floods during the rainy season and drought during the dry season. The impact is the reduction of water catchment areas around the houses of residents of Kuwaron Village RT.01 RW.04. The purpose of this activity is to provide insight and skills regarding applying appropriate techniques for porous infiltration holes. In the hope of increasing groundwater reserves, reducing inundation, and accelerating water infiltration in residents' yards. The bio-pore-making training involved several residents of Kuwaron Village. Bio pores are made with a diameter of 10 cm and a depth of 100 cm. Then, the hole filled with organic kitchen waste. That is expected to reduce organic kitchen waste from each house because porous infiltration holes containing garbage invite various soil fauna and form pores to increase groundwater infiltration. The results of the evaluation of bio pores installation for four weeks showed that the rain puddles in the residents' yards receded faster.